Pengaruh Model Pembelajaran Think Pair Share terhadap Hasil Belajar Siswa pada Tema 8 Sub Tema 2 Pembelajaran 6 di Kelas IV SD Negeri 124397 Pematang Siantar Tahun Ajaran 2022/2023 - Kristina Malau; Minar Trisnawati Lumbantobing; Esti Sirait (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of the Think Pair Share learning model on student learning outcomes in Theme 8 Sub-Theme 2 Learning 6 in Class IV SD Negeri 124397 Pematang Siantar. The type of research used is quantitative research, quantitative research is research in the form of numbers and the analysis uses statistics. The research design that will be used is experimental, with the form of Pre-Experimental Design. After seeing the total population of the study, which amounted to less than 100 people, the sample in this study were all fourth grade students, totaling 22 students. Based on test results and data analysis that has been done. The result of testing the research hypothesis is that there is a significant influence on this study from the data that has been tested. The data can be seen from the data analysis, the average results of the experimental class are obtained on the pre-test and post-test values. The results of the study are at the 0.01 level. Based on the analysis of the pretest and posttest data, it shows that the sig (2-tailed) value is 0.00 <0.05, where H0 is rejected and accepted, meaning that there is a significant difference between the learning outcomes of students using the Think model. Pair Share is more increased. Because when using this model student-centered learning (Student Centered Learning) students are more active in thinking and learning in identifying material presented in groups and then presenting the results of their discussions and then comparing them with their friends. So it can be concluded that there is an effect of using the Think Pair Share learning model on student learning outcomes as seen from the increase in the average value of learning outcomes in class IV SD Negeri 124397 Pematang Siantar for the 2022/2023 academic year.